Does ulnar variance change with age and what is the influence of training and biological characteristics in this change? A short-term longitudinal study in portuguese artistic Gymnasts - Amaral, L.; Claessens, A. L.; Ferreirinha, J.; Maia, J.; Santos, P. (Clinical Journal of Sport Medicine, 2014)
Objective: To analyze the variability and longitudinal stress-related changes in ulnar variance (UV) in a group of immature artistic gymnasts. The relationship between UV and a group of biological and training variables was also investigated.